A RCT Comparing Specific Intensive Cognitive Training to Aspecific Psychological Intervention in RRMS: The SMICT Study - Mattioli, Flavia; Stampatori, Chiara; Bellomi, Fabio; Danni, Maura; Compagnucci, Laura; Uccelli, Antonio; Pardini, Matteo; Santuccio, Giuseppe; Fregonese, Giuditta; Pattini, Marianna; Allegri, Beatrice; Clerici, Raffaella; et al. (Frontiers in Neurology, 2015)
Background: Specific cognitive rehabilitation in Multiple Sclerosis resulted to be effective compared to no treatment, although the possible role of an aspecific psychological intervention and the persistence over time of its effects have not been clearly investigated till now. Objective: The aim of the SMICT RCT was to compare the efficacy of a specific cognitive training with an aspecific psychological intervention in relapsing remitting Multiple Sclerosis patients. Methods: From a sample of 150 patients, with the same disability and immunomodulatory therapy, submitted to neuropsychological examination, 45 impaired in at least one test were included and 41 randomized to have either a specific cognitive training for the impaired function (22) or to an aspecific psychological intervention (19) for 4 months, starting after baseline examination. Neuropsycological tests and functional scales were administered at baseline and one year later. Results: After one year, the mean number of pathological tests was significantly lower in the specific treatment group, compared to the aspecific group. Memory and attention/speeded information processing functions were mostly improved. Depression and quality of life were not different between groups at follow up. Conclusions: Our study demonstrates that an intensive and domain specific cognitive approach results to be more effective than aspecific psychological intervention in patients with Multiple Sclerosis.